Experimental examination of radiation doses from cardiac and liver CT perfusion in a phantom study as a function of organ, age and sex. (18th August 2021) - Bos, Denise; König, Britta; Blex, Sebastian; Zensen, Sebastian; Opitz, Marcel; Maier, Sandra; Forsting, Michael; Zylka, Waldemar; Kühl, Hilmar; Wetter, Axel; Guberina, Nika
Abstract: Cardiac and liver computed tomography (CT) perfusion has not been routinely implemented in the clinic and requires high radiation doses. The purpose of this study is to examine the radiation exposure and technical settings for cardiac and liver CT perfusion scans at different CT scanners. Two cardiac and three liver CT perfusion protocols were examined with the N1 LUNGMAN phantom at three multi-slice CT scanners: a single-source (I) and second- (II) and third-generation (III) dual-source CT scanners. Radiation doses were reported for the CT dose index (CTDIvol ) and dose–length product (DLP) and a standardised DLP (DLP10cm ) for cardiac and liver perfusion. The effective dose (ED10cm ) for a standardised scan length of 10 cm was estimated using conversion factors based on the International Commission on Radiological Protection (ICRP) 110 phantoms and tissue-weighting factors from ICRP 103. The proposed total lifetime attributable risk of developing cancer was determined as a function of organ, age and sex for adults. Radiation exposure for CTDIvol, DLP/DLP10 cm and ED10 cm during CT perfusion was distributed as follows: for cardiac perfusion (II) 144 mGy, 1036 mGy·cm/1440 mGy·cm and 39 mSv, and (III) 28 mGy, 295 mGy·cm/279 mGy·cm and 8 mSv; for liver perfusion (I) 225 mGy, 3360 mGy·cm/2249 mGy·cm and 54 mSv, (II) 94 mGy, 1451 mGy·cm/937 mGy·cm and 22 mSv, and (III) 74 mGy, 1096 mGy·cm/739 mGy·cm and 18 mSv. The third-generation dual-source CT scanner applied the lowest doses. Proposed total lifetime attributable risk increased with decreasing age. Even though CT perfusion is a high-dose examination, we observed that new-generation CT scanners could achieve lower doses. There is a strong impact of organ, age and sex on lifetime attributable risk. Further investigations of the feasibility of these perfusion scans are required for clinical implementation.